Exosomes: Biomarkers and Therapeutic Targets of Diabetic Vascular Complications - Chen, Anqi; Wang, Hailing; Su, Ying; Zhang, Chunlin; Qiu, Yanmei; Zhou, Yifan; Wan, Yan; Hu, Bo; Li, Yanan (Frontiers in Endocrinology, 2021)
Diabetic vascular complications (DVC) including macrovascular and microvascular lesions, have a significant impact on public health, and lead to increased patient mortality. Disordered intercellular cascades play a vital role in diabetic systemic vasculopathy. Exosomes participate in the abnormal signal transduction of local vascular cells and mediate the transmission of metabolic disorder signal molecules in distant organs and cells through the blood circulation. They can store different signaling molecules in the membrane structure and release them into the blood, urine, and tears. In recent years, the carrier value and therapeutic effect of exosomes derived from stem cells have garnered attention. Exosomes are not only a promising biomarker but also a potential target and tool for the treatment of DVC. This review explored changes in the production process of exosomes in the diabetic microenvironment and exosomes’ early warning role in DVC from different systems and their pathological processes. On the basis of these findings, we discussed the future direction of exosomes in the treatment of DVC, and the current limitations of exosomes in DVC research.